2011
DOI: 10.1021/ef201380z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of NOx Control by Combustion Modifications in Pulverized Coal Utility Boiler

Abstract: Considerable research efforts focus on modeling NO x formation/destruction and predicting NO x emission so that it can be controlled. A motivation for this numerical study was to examine the efficiency of combustion modifications in the furnaces of Kostolac B 350 MWe boiler units, tangentially fired by pulverized lignite. Numerical analysis was done by an in-house developed NO x submodel, coupled with differential comprehensive combustion model, previously developed and validated. The NO x submodel focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…Numerical simulation is a powerful tool for understanding such phenomena in each furnace with a different design. Recently, numerical simulations of pulverized coal combustion field in large-scale furnaces have been conducted by various research groups [1][2][3][4][5][6][7][8][9]. For numerical simulations of pulverized coal combustion, simplified models are generally employed because of the limitation of computational resources.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation is a powerful tool for understanding such phenomena in each furnace with a different design. Recently, numerical simulations of pulverized coal combustion field in large-scale furnaces have been conducted by various research groups [1][2][3][4][5][6][7][8][9]. For numerical simulations of pulverized coal combustion, simplified models are generally employed because of the limitation of computational resources.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enable analysis of processes for NO x /SO 2 emission reduction, submodels of NO x formation/destruction reactions and Ca-based sorbent calcination/sintering/sulfation reactions were selected, coupled with the in-house developed combustion code and applied for investigation of de-NO x primary measures and de-SO 2 by Furnace Sorbent Injection (FSI) method [78][79][80][81][82][83][84][85][86]. In order to enable efficient data input and meet the real engineering needs, a new user-friendly software interface, was developed as well [80,83].…”
Section: Environmental Aspects Of Pc-fired Utility Boilers -Modellingmentioning
confidence: 99%
“…An extensive numerical study, first of its kind in Serbia, was performed for the EPS to optimize the primary measures in the tangentially fired pulverized lignite furnaces of 350 MW e TPP Kostolac B boiler units [78]. Optimal combustion modifications in the casestudy furnaces were suggested: injection of 85% of coal through the main (lower-stage) burners, local excess air control by proper distribution of preheated air between the burner tiers and the usage of finer grinding of coal, enabling over 30% of NO x emission reduction and simultaneous control of the flame position; standalone application of over-fire air provided 25% of the NO x emission abatement [79,80]. Effects of the measures on the steam boiler efficiency and safety were examined by thermal calculations, in cooperation with the Faculty of Mechanical Engineering Belgrade.…”
Section: Environmental Aspects Of Pc-fired Utility Boilers -Modellingmentioning
confidence: 99%
“…The developed sub-model of NO x formation/destruction is described in [9]. The NO x sub-model consists of reactions of fuel NO formation and depletion [10].…”
Section: No X Modellingmentioning
confidence: 99%